2000
DOI: 10.1177/0310057x0002800608
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Short-Term Ketorolac Infusion on Recovery following Laparoscopic Day Surgery

Abstract: This study tested the hypothesis that, by the addition of parenteral ketorolac to an oral analgesic regimen for one day following laparoscopic surgery, analgesia would be improved and thus the return of normal function hastened. Seventy-two female patients were randomly assigned to receive ketorolac 10.5 mg subcutaneously at the end of surgery followed by a subcutaneous infusion of 1.75 mg/h for 24 to 36 hours, or an equivalent volume of saline. All patients were provided with codeine tablets (30 mg) for analg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Two randomized clinical trials of ketorolac CSI in the postoperative setting demonstrated decreased opioid consumption after laparoscopic day surgery ( n = 33) and postcaeserean delivery ( n = 20). 13,14 Differences in ketorolac doses used in the studies and in outcome measurements preclude generalizing these data to other areas of postoperative care. This collection of literature gives insight that the analgesic effect of ketorolac is still present when given subcutaneously and that doses at slow infusion rates appear to be tolerated with minimal severe adverse effects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two randomized clinical trials of ketorolac CSI in the postoperative setting demonstrated decreased opioid consumption after laparoscopic day surgery ( n = 33) and postcaeserean delivery ( n = 20). 13,14 Differences in ketorolac doses used in the studies and in outcome measurements preclude generalizing these data to other areas of postoperative care. This collection of literature gives insight that the analgesic effect of ketorolac is still present when given subcutaneously and that doses at slow infusion rates appear to be tolerated with minimal severe adverse effects.…”
Section: Resultsmentioning
confidence: 99%
“…Campbell et al 13 completed a randomized, double-blinded, placebo-controlled study to evaluate use of subcutaneous ketorolac infusion for 24 to 36 hours following laparoscopic surgery. Four-day postoperative follow-up assessed the impact of ketorolac CSI compared to only oral opioid analgesia on return to normal function.…”
Section: Resultsmentioning
confidence: 99%
“…18,44 Data from postoperative studies of NSAIDs versus placebo given with an opioid have generally demonstrated positive results (either enhanced pain relief, reduced opioid requirements typically by 30% or more, and/or reduced opioid-related adverse effects such as nausea and vomiting) for a variety of surgical procedures including gynecologic, head and neck, thoracic, orthopedic, abdominal, spinal, and some outpatient procedures. 32,[45][46][47][48][49][50][51][52][53][54][55][56][57][58] Other studies have not shown a clear benefit of adding NSAIDs to the standard opioid pain management, although these were generally studies in which the NSAID was given one time before surgery and not continued after surgery. 44,45,53,54,[59][60][61][62][63][64][65] Nevertheless, NSAIDs still play a role as part of a balanced multimodal analgesic approach and may have particular value for major surgical procedures.…”
Section: Nonspecific Nsaidsmentioning
confidence: 99%